Search for Flavor-Changing Neutral Current Interactions of the Top Quark and Higgs Boson in Final States with Two Photons in Proton-Proton Collisions at √𝑠=13 TeV; Physical Review Letters; Vol. 129, iss. 3 - Tumasyan A. R.; Adam W. Wolfgang; Andrejkovic J. W.; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2022, 2022)
Title screen